Integration and Geographic Visualization of TKA-TPA Data Using Mapbox - Wicaksono, Bhaskoro; Asroni, Asroni; Setiawan, Asep (Universitas Muhammadiyah Yogyakarta, 2020)
TKA-TPA data management is performed conventionally and inaccurately. Accordingly, it may result in considerable data loss. Data collection for TKA-TPA by BADKO Kasihan Bantul Yogyakarta is still carried out conventionally. Therefore, this study supports BADKO TKA-TPA in data management, data reporting, data mapping, and data publication. A Web Geographic Information System (GIS) was created using the CodeIgniter framework with the Hypertext Preprocessor (PHP) programming language, MapBox on the Maps API Service, MySQL database, and the SDLC with the prototype method. The study result is a web-based GIS application. This GIS application has been successfully built and can be used by BADKO TKA-TPA Kasihan Bantul Yogyakarta for its data management and mapping system.